The Impact of TikTok eWOM on Fore Coffee Purchase Intention in Bandung - Ramadhan, Ilham Agsan; Hidayah, Riski Taufik; Alfaiza, Salsabila Aisyah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study investigates how electronic word of mouth (eWOM) on TikTok influences consumers' purchase intention toward Fore Coffee products in Bandung, Indonesia. Given the platform’s dominance among Gen Z and millennials, TikTok-based eWOM is a key digital marketing element for local brands. Using a quantitative method, data were collected through an online survey of 390 respondents who had seen TikTok content related to Fore Coffee. The research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among information quality, quantity, credibility, usefulness, adoption, and purchase intention. The results show that all dimensions of eWOM significantly affect information usefulness. In turn, information usefulness positively influences information adoption, which subsequently drives purchase intention. These findings affirm the relevance of the Information Adoption Model (IAM) in a short-form video context. This study contributes to digital consumer behavior literature by applying the IAM to TikTok, a platform characterized by user-generated content and rapid engagement cycles. The research offers practical insights for brands to enhance content credibility and usefulness in order to strengthen consumer intent to purchase.